Evaluation of Different Surface Treatments on Repair Bond Strength of Aged and Non-Aged Bulk-Fill Composites - Yıldırım, Kardelen (2026)
The aim of this study was to evaluate the effect of surface treatment and ageing on the microtensile bond strength of bulk fill composite repairs. Composite blocks were prepared using a bulk fill resin composite and divided into two groups: (A) no ageing and (B) ageing. The composite surfaces were conditioned with: (G1) control group (no surface treatment), (G2) adhesive application, (G3) phosphoric acid etching + adhesive application, (G4) phosphoric acid etching + silane + adhesive application, (G5) hydrofluoric acid etching + adhesive application, (G6) hydrofluoric acid etching + silane + adhesive application, (G7) aluminium oxide (Al2O3) sandblasting + adhesive application, (G8) Al2O3 sandblasting + silane + adhesive application. Bulk-fill substrates were then repaired with resin composite. Repaired resin blocks were cut into sticks and subjected to a microtensile test. Mechanically treated surfaces were characterized by SEM and profilometry. The highest microtensile bond strength values were obtained in group 1A. Al2O3 sandblasting followed by silane and adhesive application significantly improved microtensile bond strength values from the other ageing groups. The repair bond strength of thermal-aged bulk-fill composites is lower than non-aged composites. Silane application increased the microtensile bond strength.